Overview of Participant and Utilization of National Health Insurance by Informal Workers in Sedayu - Safirina Aulia Rahmi; Este Latifahanun; Mahardika Ratih Resti Andani; Rokhayat Rokhayat; Sarif Febriandi (Sean Institute, 2025)
The low participation of informal sector workers in the National Health Insurance (JKN) program remains a significant barrier to achieving universal health coverage in Indonesia. Despite government efforts to expand JKN participant, many informal workers remain uninsured or inactive due to various socio-economic and structural challenges. Limited awareness, financial constraints, administrative difficulties, and perceptions of health service quality contribute to low participation and service utilization. This issue is critical as informal workers make up a large proportion of Indonesia's workforce, and their exclusion from JKN coverage poses risks to individual and public health. Understanding the factors that influence JKN participation and utilization among informal workers is critical to developing targeted interventions to increase coverage and improve access to health services. This study aims to analyze the factors influencing JKN participation and service utilization among informal workers. Using a quantitative approach, data were collected from 30 respondents in Sedayu through structured questionnaires. The results indicate that only 33.3% of respondents were registered and active participants, while 53.4% were either unregistered or unaware of their enrollment status. The primary reasons for non-enrollment were the lack of JKN socialization (70%) and the perception that insurance was unnecessary due to good health (30%). Furthermore, only 40% of respondents had utilized JKN services, while 60% had never accessed them, primarily due to a lack of understanding of service procedures (45%), distant health facilities (30%), and perceived suboptimal service quality (25%). Socioeconomic factors, including income level, education, age, household size, and place of residence, significantly influenced JKN ownership, with higher-income, urban, and educated individuals being more likely to enroll. The study also highlights structural barriers such as registration complexity, service limitations, and premium affordability, which hinder participation and utilization. Addressing these issues requires enhanced socialization efforts, simplified administrative processes, improved access to healthcare facilities, and better service quality to increase JKN participation among informal workers